Implementasi Wighted Product dan TOPSIS dalam Penentuan Kualitas Sarang Walet - Kelik Sussolaikah; Wahyuni Wahyuni; Muhammad Fahmi (Pusat Riset dan Inovasi Nasional, 2022)
XYZ Store is a business that focuses on the manufacture of swallow houses as well as a place to sell swallow nests. Currently, the process of assessing the quality of swallow nests is still done manually, which often causes errors in distinguishing between good and bad nest quality. This study aims to apply the Weighted Product and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods to build a system that can determine the quality of swallow nests more accurately. This system was developed using the Laravel Framework and PHP (Hypertext Preprocessor) programming language, with XAMPP as a local server, MySQL as a database server, and Apache as a web server. System development tools include Flowchart and Entity Relationship Diagram (ERD). The results of this study indicate that the combination of the Weighted Product and TOPSIS methods can produce a more optimal assessment of the quality of swallow nests.